2014
DOI: 10.1016/j.hrthm.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Body surface localization of left and right atrial high-frequency rotors in atrial fibrillation patients: A clinical-computational study

Abstract: BACKGROUND Ablation is an effective therapy in patients with atrial fibrillation (AF) in which an electrical driver can be identified. OBJECTIVE The aim of this study was to present and discuss a novel and strictly noninvasive approach to map and identify atrial regions responsible for AF perpetuation. METHODS Surface potential recordings of 14 patients with AF were recorded using a 67-lead recording system. Singularity points (SPs) were identified in surface phase maps after band-pass filtering at the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 17 publications
(29 reference statements)
7
160
0
Order By: Relevance
“…However, as far as we know, the above‐mentioned phase mapping systems contain several limitations as follows: offline use thus requiring a long period for AF visualization, low spatial density of <4 signals/cm 2 , and insufficient verification of the imaging algorithms, resulting from poor electrode contact17 or constraints due to the inverse problem 18. Moreover, those phase mapping systems are not currently available in our country, Japan.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, the above‐mentioned phase mapping systems contain several limitations as follows: offline use thus requiring a long period for AF visualization, low spatial density of <4 signals/cm 2 , and insufficient verification of the imaging algorithms, resulting from poor electrode contact17 or constraints due to the inverse problem 18. Moreover, those phase mapping systems are not currently available in our country, Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, a dipolar distribution characterizes the surface potential maps with negative and positive time integral distributions localized in the frontal upper right and lower left quadrants, respectively. This general behaviour is also in agreement with previous computational atrial-torso models (Aslanidi et al 2011;Krueger et al 2013;Rodrigo et al 2014). However, these previous models used a simplified torso anatomy or considered only a limited number of organs what may influence the pathway followed by the electrical wavefront and then the morphology of the signals registered at the torso surface.…”
Section: Body Surface Potential Maps and P-wavessupporting
confidence: 92%
“…In this work, we have demonstrated that reconstruction errors can be mostly attributed to a loss of complexity, quantified in terms of the number of simultaneous phase singularities. This loss of complexity is consistent with a mutual cancellation of propagation wavefronts with opposed directions [10] that may not be retrievable by solving the inverse problem.…”
Section: Discussionmentioning
confidence: 62%
“…For each simulation, a uniform mesh of unipolar EGMs was calculated surrounding the epicardial surface (1 mm distance) under the assumption of a homogenous, unbounded and quasi-static conducting medium by summing up all effective dipole contributions over the entire model [10]. Computed electrograms were stored for processing at a sampling frequency of 500 Hz.…”
Section: Computational Models Of the Atria And Torsomentioning
confidence: 99%